They went from
6(15+x)=15*× to
90+6x=15x then
15x-6x=90
9x=90
X=10
And they made absolutely no attempt to explain it.
This is actually the same process that
@MarkFL used
in this post to solve this, except that the "distribution" step was performed earlier. It is in fact sufficient for demonstrating the process, as long as you can follow what happens from one step to the next.
Let's look at each item individually, then figure out what must have happened in-between...
[MATH]6 = \frac{15x}{15+x}[/MATH]
This is the problem as initially stated.
[MATH]6(15 + x) = 15x[/MATH]
This was found by multiplying both sides of the equation by [MATH]15 + x[/MATH]. Since the right side was a fraction with that as the denominator, it effectively undoes the fraction, leaving only the numerator. On the left side, it was simply a matter of multiplying with 6.
[MATH]90 + 6x = 15x[/MATH]
Here, the multiplication on the left side was performed, and the right side was left unmodified. [MATH]a(b + c)[/MATH], when distributing, becomes [MATH]ab + ac[/MATH]. The 90 comes from the fact that [MATH]6 * 15 = 90[/MATH].
[MATH]15x - 6x = 90[/MATH]
In this step, [MATH]6x[/MATH] was subtracted from both sides of the equation (giving [MATH]90 = 15x - 6x[/MATH]), then the sides were exchanged with one another. The logic is that all of the [MATH]x[/MATH] terms need to be together in order to solve for [MATH]x[/MATH].
[MATH]9x = 90[/MATH]
This is the result of subtracting [MATH]15x - 6x[/MATH] on the left, without doing anything on the right.
[MATH]x = 10[/MATH]
Finally, we divide both sides by 9 to solve for [MATH]x[/MATH].